2024
DOI: 10.1093/ismejo/wrae047
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiome feedbacks during disturbance-driven forest ecosystem conversion

Amelia R Nelson,
Timothy S Fegel,
Robert E Danczak
et al.

Abstract: Disturbances cause rapid changes to forests, with different disturbance types and severities creating unique ecosystem trajectories that can impact the underlying soil microbiome. Pile burning – the combustion of logging residue on the forest floor – is a common fuel reduction practice that can have impacts on forest soils analogous to those following high severity wildfire. Further, pile burning following clear-cut harvesting can create persistent openings dominated by non-woody plants surrounded by dense reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Our results also showed that after 13 months, the substrate composition changed dramatically compared to that at 0 months. These may be related to microbiome feedback during macadamia plant growth in these substrates [ 40 ]. Tropical peat soils are generally defined as soils formed by the accumulation of partially decayed woody plant materials under waterlogged condition [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that after 13 months, the substrate composition changed dramatically compared to that at 0 months. These may be related to microbiome feedback during macadamia plant growth in these substrates [ 40 ]. Tropical peat soils are generally defined as soils formed by the accumulation of partially decayed woody plant materials under waterlogged condition [ 41 ].…”
Section: Discussionmentioning
confidence: 99%